New instruments in the financial sector of Trinidad and Tobago. - SERGEANT, Kelvin (1996)
Notes that since the liberalization of the domestic economy since 1993, the development of new financial products have speeded up. This includes investment note certificates, asset backed securities, derivative products, investment type products and project financing facilities, although the extent of their usage remains fairly limited.